(INVITED) Opposing effects of energy migration and cross-relaxation on surface sensitivity of lanthanide-doped nanocrystals - Jingyue Fan; Liangliang Liang; Yuyang Gu; Xiaogang Liu (Optical Materials: X, 2021)
Surface sensitivity of lanthanide-doped nanocrystals has a great utility in controlling their optical properties. Surface sensitivity can be principally promoted by energy migration. Herein, we demonstrate that cross-relaxation between lanthanides makes nanocrystals less sensitive to environmental changes. We show that by codoping ytterbium ions (Yb3+) and neodymium ions (Nd3+) in hexagonal-phase sodium yttrium fluorides, surface sensitivity can be manipulated by energy transfer from Yb3+ to Nd3+. These findings enhance our understanding of surface quenching of nanocrystals and offer new opportunities in developing highly luminous nanoprobes for molecular sensing and biomedical applications.